Prevalence of Cutaneous Leishmaniasis and Identification of Vector Phlebotomus Species Leishmania in Tehsil Adenzai Dir L. Pakistan - Ihsan Ullah,Fawad Khan,Mahnoor Pervez ,Samina Yasmin,Bahar Uddin, Shahab Saqib ,Sana shahid,Faseeha Ilyas,Muhammad Usman ,Abdul Latif; inam Ullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study investigates the prevalence and distribution of Cutaneous Leishmaniasis (CL) in Tehsil Adenzai, District Dir Lower, Khyber Pakhtunkhwa, from August 2023 to February 2024, reporting a total of 1388 cases. The findings revealed a notable gender disparity, with males (82.95%) being predominantly affected, compared to females (18.05%), likely due to higher outdoor exposure and occupational risks